The significance of Sacred Groves and the impact of Urban Green spaces on Mental Health: A Study focusing on Kerala - Devika Nandakumar; Dr. Binu V.S. (Revista Electronica de Veterinaria, 2024)
The study focuses on the sacred groves and urban green spaces, solely that of Kerala, using qualitative analysis to verify the positive impact urban green spaces have on mental health and well-being. Sacred Groves being the reservoir of greenness and a haven for rare species an active communal participation can be observed in the maintenance of these places showing an apt example of human being one with nature.